PERTIMBANGAN PEMBENTUKAN PENGATURAN BESARAN MINIMAL HONORARIUM NOTARIS DALAM UNDANG – UNDANG JABATAN NOTARIS - Yudhana Eko Prasetyo (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract Notary Public Job. The base to determine the honorarium of Notary Public to be charged for the client is accorded to economical and sociological values as explained in Article 36 of Act No. 2 of 2014 about Notary Public Job. The determination of minimal honorarium Notary public profession as the national officer is not given salary by the nation but they are provided with honorarium by the client as stated in Act No.2 of 2014 under amendment against Act No. 30 of 2004 about of a notary officer, however, does not have a reliable manual because every notary profession varies, thus causing unhealthy competition. Research type is normative juridical research or normative legal research, which is that it attempts to review the regulations that have been determined for a certain law problem. The urgency to determine minimal honorarium of notary based on notary job acts shall be considered because honorarium represents a part of notary profession. Honorarium always supports the performance of notary to deliver professional work. The determination of notary minimal honorarium standard will always help to keep the professionalism of notary in walking on their profession. The formulation of ideal honorarium for notary must be based on the regulation about notary job organization where the notary organization regulation of each region will determine the minimal tariff of notary service such that the notary will find justice to accept the notary service tariff. Organizational regulation will give sanction for any violations against the minimal tariff standard of notary service in each region. Key words: consideration, regulation, conformation, minimum determination for honorarium, notary Abstrak Profesi notaris sebagai pejabat negara dalam menjalankan jabatannya tidak digaji oleh Negara melainkan mendapatkan honorarium dari kliennya diatur didalam Undang-undang No 2 Tahun 2014 perubahan atas Undang-undang No 30 Tahun 2004 tentang Jabatan Notaris.Dasar dari penetapan honorarium Notaris kepada klien berdasarkan nilai ekonomis dan sosiologis dalam Pasal 36 Undang- undang Jabatan Notaris.Dalam penetapan besaran minimal honorarium seorang Notaris belum memiliki sebuah pedoman, antara sesama profesi notaris tidak memiliki kesamaan dan cenderung ke persaingan yang tidak sehat. Penelitian ini merupakan penelitian Yuridis Normatif (Normatif Legal Research) yaitu penelitian yang dilakukan dengan cara mengkaji peraturan perundang-undangan yang berlaku atau ditetapkan pada suatu permasalahan hukum tertentu. Urgensi penetapan besaran minimal honorarium notaris dalam undang-undang jabatan notaris, seharusnya segera diatur karena honorarium merupakan bagian dari profesi notaris.Honorarium menunjang kinerja notaris agar tetap bekerja secara profesional. Penentuan standart minimal honorarium notaris akan sangat membantu menjaga profesionalitas notaris dalam menjalankan profesinya. Sedangkan formulasi penetapan honorarium bagi notaris yang ideal yaitu Sebaiknya penetapan mengenai honorarium diatur dalam peraturan organisasi jabatan notaris, di mana berlakunya penetapan peraturan organisasi notaris tersebut pada tiap regional masing-masing ditetapkan berapa tarif minimal jasa notaris, sehingga terciptanya keadilan bagi notaris dalam menerima tarif jasa notaris. Kemudian dalam peraturan organisasi tersebut dibuatkan sanksi atas pelanggaran terhadap ketentuan penetapan standar tarif minimum jasa notaris yang berlaku di tiap-tiap regional. Kata kunci: pertimbangan, pembentukan pengaturan, besaran minimal, honorarium, notaris